The Effect Of Customer Experience And Customer Satisfaction On Interest In Using Hotel Services Grand Seven One Manna - Agung Surya Pramata; Karona Cahya Susena; Eska Prima Monique Damarsiwi (Penerbit Jurnal Indonesia, 2023)
The purpose of this study was to determine the effect of customer experience and customer satisfaction on the intention to use the services of the Grand Seven One Manna hotel. The sample in this study were 90 respondents. The method used in collecting data for this research is a questionnaire. The method of data analysis in this study is the Multiple Linear Regression Research Instrument Test the Coefficient of Determination of the Hypothesis. Based on the results of this study it was concluded that customer experience has a positive and significant effect on the intention to use hotel services at Grand Seven One Manna, meaning that if the customer experience increases, the interest in using hotel services will also increase. Customer satisfaction has a positive and significant effect on the intention to use hotel services at Grand Seven One Manna, meaning that if customer satisfaction increases, the interest in using hotel services will also increase. Customer experience and customer satisfaction together have a positive and significant effect on the interest in using hotel services at Grand Seven One Manna, meaning that if customer experience and customer satisfaction increase, the interest in using hotel services will also increase.